THE EMPATHIC EMOTIONS AND SELF-LOVE IN BISHOP JOSEPH BUTLER AND THE NEUROSCIENCES - Dyck, Arthur J. (Journal of religious ethics, 2009)
In Joseph Butler, we have an account of human beings as moral beings that is, as this essay demonstrates, being supported by the recently emerging findings of the neurosciences. This applies particularly to Butler's portrayal of our empathic emotions. Butler discovered their moral significance for motivating and guiding moral decisions and actions before the neurosciences did. Butler has, in essence, added a sixth sense to our five senses: this is the moral sense by means of which we perceive what we ought or ought not do. The moral sense yields relatively reliable moral perceptions when we love our neighbors as ourselves, and when our love for ourselves is genuine. Accurate moral perceptions will be thwarted by self-deceit—that is, by a self-partiality devoid of neighbor love, a condition that thwarts genuine self-love. This essay explores the parallels between Butler's understanding of self-deceit and Robert J. Lifton's understanding of “doubling.”